Effects of nanowire texturing on the performance of Si/organic hybrid solar cells fabricated with a 2.2 μm thin-film Si absorber - He, Lining (2013)
Hybrid solar cells are fabricated by spin coating poly(3,4-ethylene-dioxythiophene):polystyrenesulfonate (PEDOT:PSS) on planar Si and Si-nanowires (SiNWs) arrays prepared by electroless chemical etching. With only a 2.2 μm thick Si absorber thin film, the short-circuit current density and power conversion efficiency (PCE) of SiNWs/PEDOT cell increase from 12.5 to 13.6 mA/cm2 and from 5.4% to 5.6%, respectively, as compared to planar Si/PEDOT cell. A maximum external quantum efficiency of 56.6% is obtained for the SiNWs/PEDOT cell. The promising PCE obtained demonstrates the potential of realizing Si/PEDOT and SiNWs/PEDOT hybrid cells using low-cost Si thin films instead of bulk Si substrate.